Improving library services to people with disabilities (Chandos Publishing, 2007)
Improving Library Services to People with Disabilities will enable librarians, policy makers and constituents to understand the importance of serving all potential patrons, recognise the best practices and model programs and learn techniques and strategies for improving the services their libraries offer